NURSES’ ADHERENCE TO THE MUNRO SCALE PRESSURE INJURY RISK ASSESSMENT - Sousa, Cristina Silva (Cogitare Enfermagem, 2023)
Objective: To measure the rate of adherence to the electronic recording of the Munro scale in the perioperative period. Method: Retrospective cohort study based on the analysis of medical records in 2022 in a large private philanthropic hospital in the city of São Paulo -BR.The completion data was extracted into an Excel report and analyzed for compliance with the scale. Results:22,743 Munro scale records were analyzed, corresponding to 11,892 electronic medical records.The adherence rate was 98.45% in the preoperative phase, 61.73% in the intraoperative phase, and 90.14% in the postoperative phase, with an average rate of 83.44%.Failures to record were related to the absence or partial completion of items on the scale and carrying out the intra- or post-operative phase without evaluating the previous phase. Conclusion: This study contributes to professional practice by showing the need for educational interventions and improvements in intraoperative processes to increase adherence to risk assessment.